The educational value of the use of forms, methods and tools of interactive methods in the organization of primary school lessons through new pedagogical technologies (Eurasian Journal of Learning and Academic Teaching, 2022)
This article analyzes the educational significance of the use of forms, methods and tools of interactive methods in the organization of primary school reading through new pedagogical technologies